Türkiye ekonomisinde finansallaşma ve büyümenin istikrarı - Karataş, Togan (My University, 2017)
Dünya ekonomisinde 1980 sonrası neoliberalizmin egemen olmasıyla ekonomiler küreselleşmiş ve dünyada finansal piyasalar öne çıkmaya başlamıştır.

After 1980, with the dominance of neoliberalism in World Economy, economies have been globalized and financial markets have begun to step forward. In recent years, this is described as financialization.
Keywords: Büyüme; Ekonomi politikası; Ekonomik durum; Finans; Finansallaşma; Growth; Turkish Economy; Türkiye; Türkiye Ekonomisi Financialization